Utilization of Drugs for Attention-Deficit Hyperactivity Disorder Among Young Patients in China, 2010–2019 - Wang, Zhiliang; Wu, Xiaoyan; Yu, Zhenwei; Yu, Lingyan (Frontiers in Psychiatry, 2022)
Objective The use of attention-deficit hyperactivity disorder (ADHD) medication is increasing worldwide but its status in China is unknown. This research aimed to assess the trends of ADHD medication use in young Chinese patients between 2010 and 2019. Methods Dispensing data related to ADHD medication use were extracted from the Hospital Prescription Analysis Cooperative Project of China. The trends in the yearly prescription number of ADHD drugs and corresponding cost were analyzed. We further stratified the data by age, sex, and specific drug. Results From 2010 to 2019, sampled prescriptions for ADHD medication increased from 902 to 4,531, and the total expenditure increased rapidly from 276,580 to 2,412,308 Chinese Yuan. Prescriptions for males were almost four-fold more than that for females. Patients aged 6–11 years had the highest number of prescriptions for ADHD medication each year, accounting for over 50% of the total number of prescriptions. The percentage of methylphenidate prescriptions decreased from 91.9% in 2010 to 76.9% in 2019, and the corresponding cost declined from 77.3% to 66.8%. In contrast, atomoxetine prescriptions increased progressively and accounted for about 24.5% of the total prescriptions at the end of the study. Conclusions The use of ADHD drugs and the corresponding cost increased rapidly in China, and methylphenidate was the most frequently prescribed medicine. The increase in ADHD prescriptions requires attention to ensure that it reflects appropriate use, especially in patients aged 6–11 years.